Their Worldview and Ours: An Exploratory Study into Pacific Peoples As Seen in New Zealand Government Policies, 1998-2013 - Katavake-McGrath, Filipo Semisi Patita (Auckland University of Technology, 2015)
This thesis is an exploratory study of the experiences of policy makers and expert policy advisors of Pacific ethnicity on the attitudes and environmental conditions that contribute to the framing of Pacific peoples’ economic wellbeing in government policies. Statistics and government reports indicate that low incomes have an adverse impact on Pacific peoples’ ability to realise economic wellbeing. Such reports imply that economic wellbeing is a construct which relies on individual households having adequate income, earned by the head/s of the household, to spend on consumable goods that help the members of the household to maximise their enjoyment. As a Tongan, raised in a family environment that was heavily influenced by the anga fakatonga (the Tongan culture), I have experienced first-hand concepts of economic wellbeing from a Tongan household perspective, which were inclined towards the sharing of money and resources across multiple households out of obligation to our wider family across the world, and also our community of Ma’ufanga in Tonga. For this study, I wanted to explore the prevalence of mainstream westernised economic logic in government policy making, and its impact on the Pacific peoples who both helped construct and lived by these policies. The methodological framework of phenomenology and talanoa was employed in this study, involving individual talanoa or key informant interviews with four participants who either held roles as policy making Minsters of the Crown, or as expert policy advisors in government departments in New Zealand between the years of 1998 and 2013. The talanoa were conducted in English and recorded. Findings were that not only was mainstream economic logic prevalent, but that the entire policy-making system represented the normative values of the New Zealand European/Palangi population. Government documents revealed, through extensive use of statistics to justify the positions of mainstream policy makers and their departments, that Pacific peoples’ economic wellbeing was typified by material hardship and difficulty in accessing adequate capital for ideal consumption. Participants revealed that despite their viewpoints clarifying the nature of resource accumulation and distribution among Pacific families, the mainstream agencies’ economic viewpoint endured, as well as the assumptions about ideal economic behaviour that were contained within. All four participants affirmed the efforts they, and many of their Pacific colleagues, had gone to, in order to affect attitudinal change inside government policy systems, and the challenges entailed in doing so. As this study only addresses a pan-Pacific and economic environment, further research is warranted.
Keywords: Pacific; Pasifika; Policy; Economic development; Neo-liberal policy; New Zealand; Deficit model; Pacific vision conference; Policy cycle; New public management; NPM; Public finance act; Public choice theory; Agency theory; Transaction cost economics; Public sector reforms; Family; Household; Resource allocation; Obligation; Talanoa; Phenomenology